SOFC stacks for mobile applications with excellent robustness towards thermal stresses. (30th October 2020) - Hagen, A.; Wulff, A.C.; Zielke, P.; Sun, X.; Talic, B.; Ritucci, I.; Frandsen, H.L.; Jensen, S.H.; Kiebach, W.R.; Hendriksen, P.V.
Abstract: Solid oxide fuel cells (SOFC) are attractive power units for mobile applications, like auxiliary power units or range extenders, due to high electrical efficiencies, avoidance of noble metals, fuel flexibility ranging from hydrogen to hydrogen carriers such as ammonia, methanol or e-gas, and tolerance towards CO and other fuel impurities. Among challenges hindering more wide-spread use are the robustness under thermal cycling. The current study employs short stacks containing anode or metal supported SOFCs, which were subjected to thermal cycles in a furnace and under more realistic conditions without external furnace. Heating from 100 °C to operating temperature was accomplished by sending hot air through the cathode compartment and heating from bottom (and top) of the stack, reaching a fastest ramping time of ca. 1 h. The stacks remained intact under severe temperature gradients of at least 20 °C/cm for anode supported and 30 °C/cm for metal supported SOFCs. Graphical abstract: Image 1 Highlights: SOFC stack design capable of delivering high power per volume and weight. Short stacks were thermally cycled using realistic strategies without furnace. 5 (anode-supported)-cell stack tolerates severe thermal gradients of 20 °C/cm. 3 (metal-supported)-cell stack tolerates severe thermal gradients of 30 °C/cm.